Venomics and antivenomics of Bothrops erythromelas from five geographic populations within the Caatinga ecoregion of northeastern Brazil - Jorge, Roberta Jeane B. (2015)
The Caatinga lancehead, Bothrops erythromelas, is a medically relevant species, responsible for most of the snakebite accidents in most parts of its distribution range in northeastern Brazil. The spectrum and geographic variability of its venom toxins were investigated applying a venomics approach to venom pools from five geographic areas within the Caatinga ecoregion. Despite its wide habitat, populations of B. erythromelas from Ceará, Pernambuco, Juazeiro, Paraiba, and Ilha de Itaparica exhibit highly conserved venom proteomes. Mirroring their compositional conservation, the five geographic venom pools also showed qualitatively and quantitatively overlapping antivenomic profiles against antivenoms generated in Vital Brazil (BR) and Clodomiro Picado (CR) Institutes, using different venoms in the immunization mixtures. The paraspecificity exhibited by the Brazilian SAB and the Costa Rican BCL antivenoms against venom toxins from B. erythromelas indicates large immunoreactive epitope conservation across genus Bothrops during the last ~ 14 million years, thus offering promise for the possibility of generating a broad-spectrum bothropic antivenom. Biological Significance Accidental snakebite envenomings represent an important public health hazard in Brazil. Ninety per cent of the yearly estimated 20-30,000 snakebite accidents are caused by species of the Bothrops genus. Bothrops erythromelas, a small, moderately stocky terrestrial venomous snake, is responsible for most of the snakebite accidents in its broad distribution range in the Caatinga, a large ecoregion in northeastern Brazil. To gain a deeper insight into the spectrum of medically important toxins present in the venom of the Caatinga lancehead, we applied a venomics approach to define the proteome and geographic variability of adult B. erythromelas venoms from five geographic regions. Although intraspecific compositional variation between venoms among specimens from different geographic regions has long been appreciated by herpetologists and toxinologists as a general feature of highly adaptable and widely distributed snake species, the five B. erythromelas populations investigated exhibit highly conserved venom proteomes. The overall toxin profile of the Caatinga lancehead's venom explains the local and systemic effects observed in envenomations by B. erythromelas. The five geographic venom pools sampled also showed qualitatively and quantitatively overlapping antivenomic profiles against antivenoms generated using different bothropic venoms in the immunization mixtures. The large immunoreactive epitope conservation across genus Bothrops offers promise for the generation of a broad-spectrum bothropic antivenom.